An Attribution Analysis of Responsibility Assessment for Audit Performance - Arrington, C. Edward; Bailey, Charles D.; Hopwood, William S. (Journal of Accounting Research, 1985)
C. Edward Arrington, Charles D. Bailey, William S. Hopwood, An Attribution Analysis of Responsibility Assessment for Audit Performance, Journal of Accounting Research, Vol. 23, No. 1 (Spring, 1985), pp. 1-20